Thermodynamic optimization of irreversible heat pumps - Sarkar J.; Bhattacharyya S.; Ramgopal M. (My University, 2025)
The performance of an irreversible heat pump for simultaneous cooling and heating applications, for which irreversibilities results from both the finite size and finite rate of heat conduction, as well as compression and expansion, is studied. The relation between optimum system coefficient of performance and optimal rate of combined cooling and heating output has been established. Also relations for optimal cold and hot fluid temperatures have been derived and performance of irreversible heat pump has been discussed. The optimal correlations have been simplified for endoreversible cycle and compared with the relation for only cooling or heating in the literature. Consequently, optimal relations for heat conductance inventory, residence time and mass distribution between the heat exchangers have been established.